Makna Semangat Melayani Negeri bagi Aparatur Dinas Perhubungan Provinsi Sulawesi Tenggara dalam Meningkatkan Kualitas Pelayanan Publik - Roys Sutrisno; Maudhy Satyadharma; Sri Wulan Dwi Octaviani; La Ode Muhamad Akbar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the meaning of the theme for National Awakening Day 2026, “Rise Together, Realize a Strong Indonesia,” for officials at the Southeast Sulawesi Provincial Transportation Agency, as well as its implications for improving the quality of public services. The study employs a descriptive qualitative approach through participatory observation, in-depth interviews, and document analysis involving both leadership and service staff. The findings indicate that the spirit of serving the nation is interpreted as a moral commitment that reinforces professionalism, discipline, loyalty, responsibility, and a service-oriented focus toward the community. This interpretation is manifested through strengthened work collaboration, responsive service behavior, more effective organizational coordination, and sustained efforts to improve service performance. Leadership, organizational culture, recognition of performance, and the utilization of technology are key factors supporting public service transformation. However, infrastructure limitations, the geographical characteristics of the archipelago, digital competency gaps, and increasing service demands remain challenges in its implementation. These findings underscore that strengthening the values of public service, human resource capacity, and organizational resilience are essential prerequisites for achieving adaptive, sustainable, and community-oriented public service.